Asaia spp. exposure for improving mosquito mass-rearing, and the effects on Culex pipiens pipiens vector competence for West Nile virus - Alessandro Roman; Charlotte Linthout; Ben Raymond; Constantianus J. M. Koenraadt (PLoS ONE, 2025)
Various vector control strategies are in place to reduce the spread of arthropod-borne viruses. Some of these, such as application of insecticides, are encountering operational challenges and a reduced overall effectiveness due to evolution of resistance. Alternative approaches for mosquito population control, such as the sterile insect technique, depend on efficient mass-rearing of healthy mosquitoes prior to mass-release in the field. Therefore, improving efficiency and quality of mass-rearing techniques is crucial to obtain fit mosquitoes. Previous studies have shown that Acetic Acid Bacteria of the genus Asaia can have a mutualistic effect on larval development in different mosquito species and can thus contribute to improved rearing output. However, whether improved performance in the larval stages may have knock-on effects in the adult stage, for example by increasing their capability to transmit arbovirus, remains unclear. Such effects may jeopardize future control efforts. We tested the effects of two Asaia species, Asaia krungthepensis and Asaia bogorensis, on development time and adult size under two rearing conditions: individual rearing and group rearing of Culex pipiens larvae. Besides investigating development and size, we also investigated whether Asaia spp. exposure during the larval stage can influence the vector competence of Culex pipiens pipiens for West Nile virus (WNV). Our work shows the potential of improving mass-rearing efficiency by employing Asaia krungthepensis as a mutualist for Culex pipiens pipiens. Importantly, this study reveals no significant increase in dissemination and transmission rate of WNV by Culex pipiens pipiens when inoculated with Asaia spp., although an increase in viral titer in the legs and the saliva was observed when the mosquitoes were inoculated with the two Asaia species. Interestingly, we confirmed that Asaia spp. bacteria did not establish as a permanent member of the microbiota of Culex pipiens pipiens. As Asaia spp. did not establish in adult mosquitoes, the observed change in WNV titers can be a result of indirect interactions of Asaia with the native Culex pipiens pipiens microbiome. Our results stress the importance of carefully evaluating host-symbiont interactions to avoid the potential of releasing mosquitoes with enhanced vector competence.